DEFINING SPEECH OR VERBAL CHARACTERIZATION OF A SCENIC CHARACTER - CIOBANU LUCIA (Studiul Artelor şi Culturologie: Istorie, Teorie, Practică, 2019)
Speaking differs from person to person depending on their temperament, physical constitution, character, appearance, profession, intelligence, occupation, the circle of friends, their attitude to the surrounding world, and to themselves. People speak with particularities specific to their geographical area, the type of work they do, their age, and, finally, according to their state at the time of the speech. We take these nuances into account when verbally building the scenic character. Hence, characters have different vocabularies, different modes of speaking, accentuating syllables, words, having individual speech tempos, according to their characters. This is that defining speech, which differentiates one person from another, one character from another